Building a Sakinah Family through the Rahmat Pura Wedding Tradition - Wulida Ainur Rofiq,; Khoirul Anwar,; Abdillah Afabih, (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2022)
Realizing a sakinah family is the dream of every married couple. A family full of love and affection. The occurrence of mutual understanding and good understanding and able to overcome any conflicts in the family. It takes a lot of effort and many factors influence it. In the Islamic Boarding School, the Source of Mental Education in the Religion of Allah, there is a tradition of mass marriages called Rahmat Pura. This marriage has interesting stages because it has values ​​and goals to create a sakinah family. This study uses a phenomenological approach, examining the consciousness experience of each individual through identifying the essential qualities of the consciousness experience by conducting in-depth research on the mass marriage of Rahmat Pura. As a result, families who marry through the stages of the Rahmat Pura mass marriage are able to realize a sakinah family thanks to following the stages in the Rahmat Pura mass marriage.